2007
DOI: 10.1099/mic.0.2007/008441-0
|View full text |Cite
|
Sign up to set email alerts
|

Propionate inactivation of butane monooxygenase activity in ‘Pseudomonas butanovora’: biochemical and physiological implications

Abstract: Butane monooxygenase (BMO) catalyses the oxidation of alkanes to alcohols in the alkane-utilizing bacterium 'Pseudomonas butanovora'. Incubation of alkane-grown 'P. butanovora' with butyrate or propionate led to irreversible time-and O 2 -dependent loss of BMO activity. In contrast, BMO activity was unaffected by incubation with lactate or acetate. Chloramphenicol inhibited the synthesis of new BMO, but did not change the kinetics of propionate-dependent BMO inactivation, suggesting that the propionate effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This avoids induction by compounds that are not substrates for BMO. Propionate, the final product of propane oxidation, acts as a potent repressor of BMO operon transcription (Doughty et al ., 2006) and as a direct inhibitor of BMO activity (Doughty et al ., 2007), an effect that persists until propionate catabolism is induced. Propionate catabolism is inactive during growth on butane, but is activated by propionate or upon growth on propane or pentane.…”
Section: Regulation Of Alkane‐degradation Pathwaysmentioning
confidence: 99%
“…This avoids induction by compounds that are not substrates for BMO. Propionate, the final product of propane oxidation, acts as a potent repressor of BMO operon transcription (Doughty et al ., 2006) and as a direct inhibitor of BMO activity (Doughty et al ., 2007), an effect that persists until propionate catabolism is induced. Propionate catabolism is inactive during growth on butane, but is activated by propionate or upon growth on propane or pentane.…”
Section: Regulation Of Alkane‐degradation Pathwaysmentioning
confidence: 99%
“…For example, expression of BMO in P. butanovora is repressed by propionate, a downstream metabolite of propane oxidation (Doughty et al, 2006). Moreover, propionate acts as a repressor of alkane degradation in P. butanovora by competitive inhibition for the BMO catalytic site (Doughty et al, 2007). It has been shown that expression of BMO-encoding genes is activated by the putative sigma (54)-transcriptional regulator BmoR.…”
Section: Genes and Enzymes Participating In Aerobic Degradation Of Hymentioning
confidence: 99%
“…The mechanism of action of propionate, another BMO inhibitor, was studied using these mutants. It was shown that both reversible inhibition and inactivation of BMO occurred with propionate because some but not all activity could be recovered by washing of the cells to remove the propionate 47c. Although reversible inhibition was seen with all mutants tested, only those mutants close to the active site had any effect on the irreversible inactivation of BMO by propionate.…”
Section: Sdimo Enzymes – Diversity and Mutagenesis Studiesmentioning
confidence: 99%
“…Irreversible inactivation of the BMO enzyme by propionate may be via coordination of the aliphatic tail of propionate to Fe ions at the active site, resulting in the uncoupling of O 2 activation from substrate oxidation and leading to the formation of H 2 O 2 , which damages the enzyme. Interestingly, sMMO is not inactivated by propionate and so this is another MMO‐like phenotype displayed by the G113N mutant 47c…”
Section: Sdimo Enzymes – Diversity and Mutagenesis Studiesmentioning
confidence: 99%